Cost-effectiveness of total hip arthroplasty versus resurfacing arthroplasty: economic evaluation alongside a clinical trial. Issue 5 (12th October 2012) - Edlin, Richard; Tubeuf, Sandy; Achten, Juul; Parsons, Nicholas; Costa, Matthew
Abstract : Objective: To report on the relative cost-effectiveness of total hip arthroplasty and resurfacing arthroplasty (replacement of articular surface of femoral head only) in patients with severe arthritis suitable for hip joint resurfacing arthroplasty. Design: Cost-effectiveness analysis on an intention-to-treat basis of a single-centre, single-blind randomised controlled trial of 126 adult patients within 12 months of treatment. Missing data were imputed using multiple imputations with differences in baseline quality of life and gender adjusted using regression techniques. Setting: A large teaching hospital trust in the UK. Participants: A total of 126 adult patients with severe arthritis of the hip joint suitable for a resurfacing arthroplasty of the hip. Results: Data were received for 126 patients, 4 of whom did not provide any resource use data. For the remainder, data were imputed for costs or quality of life in at least one time point (baseline, 3, 6 months and 1 year) for 18 patients. Patients in the resurfacing arm had higher quality of life at 12 months (0.795 vs 0.727) and received 0.032 more QALYs within the first 12 months postoperation. At an additional cost of £564, resurfacing arthroplasty offers benefits at £17 451 per QALY within the first 12 months of treatment. When covariates are considered, the health economic case is stronger in men than in women. Conclusions: Resurfacing arthroplasty appears to offer very short-term efficiency benefits over total hip arthroplasty within a selected patient group. The short-term follow-up in this trial should be noted, particularly in light of the concerns raised regarding adverse reactions to metal debris from metal-on-metal bearing surfaces in the longer term. Longer-term follow-up of resurfacing arthroplasty patients and decision analytic modelling is also advised. Trial registration: Current controlled Trials ISRCTN33354155 . UKCRN 4093.